Grasberg block cave mine rail project update – PT Freeport Indonesia - Lara, F; Brannon, C; Hariyadi, A; Castro, M; Gillman, J (MassMin 2020: Proceedings of the Eighth International Conference & Exhibition on Mass Mining, 2020)
The Grasberg Block Cave (GBC) mine has implemented an automated train ore haulage system for transporting production ore from multiple chute galleries to the underground crushers. This paper provides an update of the current operations; commissioning activities and rail expansion plans during production ramp up; an overview of lessons learned during the rail commissioning; and expected operational challenges. The key to the success of the GBC rail haulage system is to manage all of these challenges in an efficient way so that the production targets can ultimately be achieved. The GBC rail haulage design comprises approximately 23 km of rail (comprising sections of both ballasted and embedded track) and 117 chutes to load ore to the ore cars and deliver the ore to three unloading stations above the crushing-conveying system. Currently, 26 chutes are operating and 8 are under construction or on commissioning phase. Ore is currently being delivered to one operating unloading station, while a second station will be commissioned in 2021. The rail system is designed to operate in full-automated mode, including chute selection, loading, hauling and dumping. Chute loading operation is done remotely from the surface control room. Trains consist of 11 bottom-dump 20 m3 ore cars driven by a 40-tonne driverless electric locomotive. Approximately 10 to 12 trains and one spare train are required to maintain full production. To date, three trains are available on site for the current mine operations and control systems commissioning. The GBC rail project has been divided into five stages based on the current production schedule. Current development and construction activities are focused on finalizing the required haulage infrastructure during the early years of production. At the same time, detailed engineering and procurement of long lead-time items are progressing to ensure that the production ramp up at GBC is not at risk due to a delayed rail haulage system. Stages 2 and 3 of the rail system are expected to be commissioned by 2020, followed by stage 4 in 2021/2022.